Finding and using secondary data - Stieglitz, Tara (My University, 2026)
Learn how to bolster your research using secondary data from open data sources and databases the library subscribes to.
Presented on February 12, 2026, at Love Data Week 2026 at MacEwan University in Edmonton, Alberta.
Keywords: secondary data; open data sources; Love Data Week workshop